(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2026)
This article extends the analysis of meaning-making in communication by introducing the concept of framing. Drawing on interdisciplinary traditions from sociology, artificial intelligence, semantics, and linguistics, it conceptualizes a frame as a structured portion of background knowledge related to a specific area of the environment. Frames guide communication, shape behavioral expectations, support inferences, and are closely linked to particular lexical and grammatical choices.